Decolonizing Character Representation: A Postcolonial Analysis of Race-Swapping in Disney’s The Little Mermaid Movie (2023) - Tano, Andreas; Simanjuntak, Immanuel Sheva (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2024)
This article investigates the implications of race-swapping character representation in the 2023 live-action adaptation of Disney's